1995
DOI: 10.1002/chem.19950010112
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Selective Chelating Agents: 1,3,5‐Trideoxy‐1,3,5‐tris‐(dimethylamino)‐cis‐inositol, a Powerful Ligand for Hard and Highly Charged Metal Ions

Abstract: A series of compounds containing the mononuclear complexes [M(tdci),13Ge, Sn) was prepared and characterized by elemental analysis, NMR spectroscopy, and FAB mass spectrometry. Characteristic fragmentation reactions in the mass spectra were elucidated. X-ray analysis of the Al"', Fe"', Ga"' , and In"' complexes revealed that two neutral, zwitterionic tdci ligands coordinate to the metal cation exclusively through deprotonated alkoxo groups. The six coordinated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 28 publications
7
50
1
Order By: Relevance
“…These properties are in agreement with the elongation of the MN 6 core along the pseudotrigonal axis. 28 A similar relationship has previously been observed between the structural parameters of bis-taci complexes with an MO 6 coordination. It is interesting, however, that there is no obvious correlation between the C-N-M bond angle and the metal ion size.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…These properties are in agreement with the elongation of the MN 6 core along the pseudotrigonal axis. 28 A similar relationship has previously been observed between the structural parameters of bis-taci complexes with an MO 6 coordination. It is interesting, however, that there is no obvious correlation between the C-N-M bond angle and the metal ion size.…”
supporting
confidence: 67%
“…In fact, the oxygen donors of taci are only effective in metal binding if they are deprotonated. 28 For the Co III complex 5, coordination to alkoxo groups is even possible in acidic media, since the noncoordinated amino groups act as an internal base, facilitating the deprotonation of the oxygen donors and generating a zwitterionic form of taci. However, it has recently been shown that, in the case of the divalent Mg 2+ , Ca 2+ , Sr 2+ , and Ba 2+ , the coordinated hydroxy groups are not sufficiently acidic to cause such a proton transfer from O to N and they remain protonated.…”
Section: Preparation and Crystal Structure Of [M(taci) 2 ] 2+ Complexesmentioning
confidence: 99%
“…In terms of simple VSEPR (valence shell electron pair repulsion) considerations, one would expect strict O h symmetry for an unstrained GeO 6 moiety. Regarding some negative charges on the alkoxo donors, enhanced ligand-ligand repulsion should result in an increase of interligand OÁ Á ÁO distances (Hegetschweiler et al, 1995). As a matter of fact, in all our previous investigations, the interligand OÁ Á ÁO separations have been found to be larger than the corresponding intraligand distances throughout.…”
Section: Resultsmentioning
confidence: 56%
“…Unfortunately, ES-MS data allowing the confirmation of this 1:1 binding mode between L and Al 3þ ions could not be obtained from solution containing L and Al 3þ . Similarly to the corresponding complex formed with Taci and other derivatives [36][37][38], the formation of a unique electrochemical signal around þ 175 mV indicates that the hard metal cation is coordinated by the alkoxo groups of L, the protons of the hydroxyl groups in L being transferred to the amino groups with formation of ammonium subunits.…”
Section: Electrochemical Behavior Of L In the Presence Of Al 31 Cationsmentioning
confidence: 96%